Illuminating insights into subjectivity: Q as a methodology in applied linguistics research - Thumvichit A. (2023)
Applied linguistics (AL) is a broad field of study that often concerns subjective domains such as beliefs, opinions, perspectives, values and emotions. Q methodology (Q), a mixed methods approach to phenomenological and typological inquiry, is specifically designed to help researchers better understand individuals' subjective viewpoints. Although Q has existed for eight decades, it rarely intersects with language-related research. This article offers AL researchers an overview of Q and examples of its application. The overview covers its brief history and underlying theoretical concepts. The application is illustrated using a case exemplar that investigates language learners' perspectives regarding enjoyment in online learning. The advantages and limitations of Q are also discussed. There is plenty of room for AL researchers to advance Q, both as a standalone methodology and as an accompaniment to other methods.